2020
DOI: 10.3892/mmr.2020.11376
|View full text |Cite
|
Sign up to set email alerts
|

Erastin induces apoptotic and ferroptotic cell death by inducing ROS accumulation by causing mitochondrial dysfunction in gastric cancer cell HGC‑27

Abstract: erastin, a classical inducer of non-apoptotic cell death, exerts cytotoxicity in several types of cancer cells, including gastric cancer cells, by depleting glutathione, which is a primary cellular antioxidant, thus causing reactive oxygen species (roS) accumulation. although numerous studies have focused on the non-apoptotic cell death induced by erastin, whether erastin induces apoptosis remains unknown. The present study confirmed the cytotoxicity of erastin in HGC-27 cells and used a 30% inhibitory concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 18 publications
(23 reference statements)
1
24
0
Order By: Relevance
“…In our previous study [ 10 ], we showed that genetic disruption of the xCT transporter in pancreatic ductal adenocarcinoma (PDAC), one of the most aggressive types of cancer with a dismal 5-year survival rate of 7% [ 11 ], promotes intracellular cysteine depletion, inhibition of GSH synthesis followed by accumulation of membrane lipid hydroperoxides and finally, ferroptotic cell death in vitro. Similar results have been observed with pharmacological inhibition of xCT by erastin in a variety of cancers including breast, liver, gastric and pancreatic tumors [ 12 , 13 , 14 , 15 ]. However, in the same study our group demonstrated that, contrasting with the in vitro results, xCT-depleted PDAC cell xenografts in mice were able to grow at the same rate as their wild type (WT) counterparts, albeit with a slight delay.…”
Section: Introductionsupporting
confidence: 84%
“…In our previous study [ 10 ], we showed that genetic disruption of the xCT transporter in pancreatic ductal adenocarcinoma (PDAC), one of the most aggressive types of cancer with a dismal 5-year survival rate of 7% [ 11 ], promotes intracellular cysteine depletion, inhibition of GSH synthesis followed by accumulation of membrane lipid hydroperoxides and finally, ferroptotic cell death in vitro. Similar results have been observed with pharmacological inhibition of xCT by erastin in a variety of cancers including breast, liver, gastric and pancreatic tumors [ 12 , 13 , 14 , 15 ]. However, in the same study our group demonstrated that, contrasting with the in vitro results, xCT-depleted PDAC cell xenografts in mice were able to grow at the same rate as their wild type (WT) counterparts, albeit with a slight delay.…”
Section: Introductionsupporting
confidence: 84%
“…The induction of ferroptosis is mainly based on the Fenton reaction, wherein the accumulated iron (II) is oxidized into iron (III) by hydrogen peroxide, and lipid peroxides are in turn converted into ROS hydroxyl radical) [92]. Our results indicate that KR might be a potential inducer of ferroptosis and acts similar to erastin by inducing apoptotic cell death through ROS accumulation [94]. In contrast, Hu et al [93] demonstrated that ferroptosis might play an important role in the resistance of gliomas to temozolomide, which might be confirmed on the basis of the results obtained after 7-deazaKR treatment.…”
Section: Discussionmentioning
confidence: 70%
“…Lipid peroxidation associated to ferroptosis could be an alternative cell-death mechanism, nevertheless Caspase activation has not been described in ferroptosis cell-death [41]. Simultaneous activation of some cell death mechanisms has been already observed [42,43]. We postulate that Caspase-3 activation could be the final step of an alternative/mixed cell-death mechanism, although pyroptosis could not be excluded as an alternative SA-induced cell-death mechanism.…”
Section: Discussionmentioning
confidence: 73%